Social Entrepreneurship an Effort to Eradicate Poverty - Saleem, Muhammad Saad; Selvadurai, Rinosha a/p M; Damodoran, Yadu K.; Priyatmono, Budi (Politeknik Ilmu Pemasyarakatan, 2024)
The term social entrepreneurship is used to refer to the rapidly growing number of organizations that have been created for the benefit of society. Social entrepreneurs have created models for efficiently catering to basic human needs that existing markets and institutions have failed to satisfy. Social entrepreneurship combines the resourcefulness of traditional entrepreneurship with a mission to change society. Social entrepreneurship offers insights that may stimulate ideas for more socially acceptable and sustainable business strategies and organizational forms. Because it contributes directly to internationally recognized sustainable development goals, social entrepreneurship may also encourage established corporations to take on greater social responsibility. Akhuwat is an organization established to contribute to society in several dimensions that are associated with economic and social aspects. The mission of Akhuwat is to reduce poverty in the country. The paper will argue that social entrepreneurship ventures such as Akhuwat are able to overcome the hurdles to socio-economic and sustainable development in poor countries by building necessary infrastructure, creating social capabilities to respond to economic opportunity and discovering and creating the conditions for scaling up and for financial viability. Thus, this paper will highlight the impact of Akhuwat in reducing poverty and enhancing economic and social status of the beneficiaries of Akhuwat.